Chinese anti-Westernism on social media - Lehman-Ludwig, A; Burke, A; Ambler, D; Schroeder, R (SAGE Publications, 2023)
The Chinese Communist Party and its supporters are increasingly using social media platforms to shape China’s public image. This online image is a means of strengthening domestic nationalism and of projecting “soft power” abroad. This paper examines various forms of anti-Westernism that are central to this image-making. It analyzes several recent topics—the Belt and Road Initiative, climate change, the COVID-19 vaccine, the Beijing Olympics, and the conflict in Ukraine—on the r/Sino subreddit page of Reddit and compares them with two online news outlets, the South China Morning Post and China Daily. The paper focuses on how these media frame the contest between a rising China and a failing West, so creating a discourse that competes with the negative portrayals of China outside the country. The paper contrasts the aggressive strengthening of China’s image against the West on social media with more sober accounts of the same topics in China’s official media and in commercial news outlets. The contribution of the paper is to document an emerging online anti-Westernism that is playing an increasing role in the changing geopolitical landscape.